Privacy‐preserving targeted mobile advertising: requirements, design and a prototype implementation. (21st April 2016) - Liu, Yang; Simpson, Andrew
Summary: With the continued proliferation of mobile devices, the collection of information associated with such devices and their users—such as location, installed applications and cookies associated with built‐in browsers—has become increasingly straightforward. By analysing such information, organisations are often able to deliver more relevant and better focused advertisements. Of course, such targeted mobile advertising gives rise to a number of concerns, with privacy‐related concerns being prominent. In this paper, we discuss the necessary balance that needs to be struck between privacy and utility in this emerging area and propose privacy‐preserving targeted mobile advertising as a solution that tries to achieve that balance. Our aim is to develop a solution that can be deployed by users but is also palatable to businesses that operate in this space. This paper focuses on the requirements and design of privacy‐preserving targeted mobile advertising and also describes an initial prototype. We also discuss how more detailed technical aspects and a complete evaluation will underpin our future work in this area. Copyright © 2016 John Wiley & Sons, Ltd.